Tajārib Ibdāʻīyah fī Tadrīs Mahārat al-Muḥādathah bi-Kullīyat al-Sulṭān Qābūs li-Taʻlīm al-Lughah al-ʻArabīyah lil-Nāṭiqīn bi-Ghayrihā - Saʻdī, ʻUthmān ibn Mūsá (al-Muʼtamar al-Duwalī: al-Dawr al-ʻUmānī fī Khidmat al-Lughah al-ʻArabīyah, 2015)
In response to the daily increasing demand from learners of Arabic as a foreign language, and in keeping with the will of Sultan Qaboos bin Said regarding Arabic and its civilizational and epistemic value, the Sultan Qaboos College for Teaching Arabic to Speakers of Other Languages was founded at Manaḥ in the Sultanate of Oman. Its aims are to offer quality Arabic programmes for non-native speakers within an authentic linguistic and cultural environment; to prepare learners with a basic command of Arabic skills enabling them to engage with contemporary Arab culture; to spread awareness of the importance of teaching Arabic to non-native speakers in building bridges of cooperation and cultural exchange among peoples; to give non-Arabic speakers the opportunity to acquire the language and to continue their studies in institutions that use Arabic as the medium of instruction; to contribute to spreading Arabic among peoples and acquainting them with Arab-Islamic civilization; and to make known the cultural, social and civilizational heritage of the Sultanate. Reinforcing the work done in the college's short life, this paper sets out its experience in teaching the conversation skill, the efforts made in that field, and the exchange of this experience with specialists.
MHF-ARABICLANG-011
Keywords: Arabic as a foreign language; Speaking skills; Language pedagogy; Sultan Qaboos College; Oman